2019
DOI: 10.1111/are.14303
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some haemolymph biochemical properties and F‐cell prevalence in hepatopancreas of white leg shrimp (Litopenaeus vanammei) after fed diets containing apple cider vinegar and propionic acid

Abstract: The present study aimed to evaluate the effect of dietary ACV (apple cider vinegar) and PA (propionic acid) supplementation on some biochemical properties of haemolymph and fibrillar cell (F‐cell) number in the hepatopancreas of shrimp. Five different diets supplemented with 0%, 1%, 2%, 4% ACV and 0.5% PA diets were fed to Litopenaeus vanammei. Some biochemical parameters of haemolymph (cortisol, alkaline phosphatase, albumin, urea, uric acid, creatinine, phosphorus, total hemocyte count) and prevalence of F‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Alanine aminotransferase, AST and ALP are key cellular metabolic enzymes that play an important role in protein metabolism. These enzymes are considered a reliable indicator of hepatopancreas health in crustaceans (Pourmozaffar, Tamadoni Jahromi, et al, 2019). Our results indicated that the addition of paprika extract to the diet had no effect on the activity of AST and ALP enzymes in the haemolymph.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alanine aminotransferase, AST and ALP are key cellular metabolic enzymes that play an important role in protein metabolism. These enzymes are considered a reliable indicator of hepatopancreas health in crustaceans (Pourmozaffar, Tamadoni Jahromi, et al, 2019). Our results indicated that the addition of paprika extract to the diet had no effect on the activity of AST and ALP enzymes in the haemolymph.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes are considered a reliable indicator of hepatopancreas health in crustaceans (Pourmozaffar, Tamadoni Jahromi, et al, 2019).…”
mentioning
confidence: 99%
“…Additionally, the number of Vibrio spp., R‐cells (lipid storage cells) of hepatopancreas and cholesterol level, triglyceride concentration and total heterotrophic marine bacteria was reduced in white shrimp. Pourmozaffar et al 52 also reported that ACV and propionic acid resulted in increased albumin concentration, total hemocyte count, phosphorus concentration, haemolymph cortisol, urea, uric acid, creatinine, ALP and tubule area.…”
Section: The Effects Of Apple By‐products and Derivatives On The Perf...mentioning
confidence: 98%
“…Phytochemicals are environment-friendly products, and containing bioactive ingredients that contribute to many physiological functions in aquatic animals (Zhu, 2020). Furthermore, the beneficial effects of herbs have been the subject of many studies in fish and crustaceans (Soosean et al, 2010;Wu et al, 2015;Pourmozaffar et al, 2019). Grape seeds are produced in grape juice industry, and winery (Grosu et al, 2019).…”
mentioning
confidence: 99%